Binding affinity of asiatic acid derivatives design against Inducible Nitric Oxide Synthase and ADMET Prediction - RE Kartasasmitaa, I Musfiroha & b, A Muhtadib, S Ibrahima (Journal of Applied Pharmaceutical Science, 2014)
Asiatic acid (AA) is a pentacyclic triterpenoid compound isolated from pegagan (Centella asiatica) and is reported to show anti-inflammatory activities by inhibiting inducible nitric oxide synthase (iNOS), an isoenzyme responsible for the catalysis of nitric oxide formation. The aim of this study was to obtain information regarding binding affinity of some potential asiatic acid derivatives to iNOS as well as pharmacokinetic properties including oral absorption, distribution, metabolism, and toxicity (ADME/T) using in silico methods. Twelve AA derivatives that were produced by modeling of AA on A- or C-ring or its carboxylic acid group, were included in this study. The affinities of these compounds were studied using molecular docking methods, while pharmacokinetic properties were studied using the PreADMET online program. The results showed that eight AA derivative designs have lower free energy binding (FEB) in comparison to AA (–9.79 kcal/mol), while four of the compound designs showed higher FEB than AA. 2,3-dioxo-11,13 diene-23-carboxy asiatic acid (7) showed the lowest FEB of -11.33 kcal/mol. This compound has the human intestinal absorption (HIA), Caco-2 cell permeability, and plasma protein binding values of 96.62%, 20.90 (nm/Sec.), and 98.46%, respectively, which are comparable to those of AA and other AA derivatives. It is concluded that 2,3-dioxo-11,13 diene-23-carboxy asiatic acid (7) is an AA derivative with potential to be developed as a potential iNOS inhibitor.
Keywords: Asiatic acid derivatives, ADME/T, iNOS, binding affinity.